Early Developmental Trajectories of Functional Connectivity Along the Visual Pathways in Rhesus Monkeys. (1st October 2018) - Kovacs-Balint, Z; Feczko, E; Pincus, M; Earl, E; Miranda-Dominguez, O; Howell, B; Morin, E; Maltbie, E; LI, L; Steele, J; Styner, M; Bachevalier, J; et al.
Abstract: Early social interactions shape the development of social behavior, although the critical periods or the underlying neurodevelopmental processes are not completely understood. Here, we studied the developmental changes in neural pathways underlying visual social engagement in the translational rhesus monkey model. Changes in functional connectivity (FC) along the ventral object and motion pathways and the dorsal attention/visuo-spatial pathways were studied longitudinally using resting-state functional MRI in infant rhesus monkeys, from birth through early weaning (3 months), given the socioemotional changes experienced during this period. Our results revealed that (1) maturation along the visual pathways proceeds in a caudo-rostral progression with primary visual areas (V1–V3) showing strong FC as early as 2 weeks of age, whereas higher-order visual and attentional areas (e.g., MT–AST, LIP–FEF) show weak FC; (2) functional changes were pathway-specific (e.g., robust FC increases detected in the most anterior aspect of the object pathway (TE–AMY), but FC remained weak in the other pathways (e.g., AST–AMY)); (3) FC matures similarly in both right and left hemispheres. Our findings suggest that visual pathways in infant macaques undergo selective remodeling during the first 3 months of life, likely regulated by early social interactions and supporting the transition to independence from the mother.